Generating a Bispecific Antibody Drug Conjugate Targeting PRLR and HER2 with Improving the Internalization - Hui-Fang Zong; Bao-Hong Zhang; Jian-Wei Zhu (Georg Thieme Verlag KG, 2022)
Antibody drug conjugate (ADC) therapy has become one of the most promising approaches in cancer immunotherapy. The bispecific targeting could improve the specificity, affinity, and internalization of the ADC molecules. Prolactin preceptor (PRLR) and HER2 have crosstalk signaling in breast cancer, and PRLR undergoes a rapid internalization compared with HER2. To improve the efficacy of HER2 ADCs with enhancing the target specificity and internalization, we constructed a PRLR/HER2-targeting bispecific ADC (BsADC). We evaluated the characterization of PRLR × HER2 BsADC from the affinity and internalization, and further assessed its in vitro cytotoxicity in human breast-cancer cell lines (BT474, T47D, and MDA-MB-231) using Cell Count Kit-8 analysis. Our data demonstrated that PRLR × HER2 BsADC kept the affinity to two targeting antigens after conjugating drugs and exhibited higher internalization efficiency in comparison to HER2 ADC. Furthermore, PRLR × HER2 BsADC demonstrated to have superior antitumor activity in human breast cancer in vitro. In conclusion, our findings indicate that it is feasible through increasing the internalization of target antibody to enhance the antitumor activity and therapeutic potential that could be further evaluated in in vivo animal model.